2018
DOI: 10.1007/s12039-018-1529-x
|View full text |Cite
|
Sign up to set email alerts
|

A tetranuclear iron complex: substitution with triphenylphosphine ligand and investigation into electrocatalytic proton reduction

Abstract: The reaction of the tetranuclear iron complex [μ 4-Sulfido-bis{(μ-2-furylmethanethiolato) bis[tricarbonyliron](Fe-Fe)}] 1 with PPh 3 was explored. The reaction leads to the formation of the monosubstituted complex [Fe 2 (μ-2-furylmethanethiolate) 2 (CO) 5 (PPh 3)] 2. X-ray crystal structure has been reported for complex 2. Complexes 1 and 2 were found to be active catalysts for proton reduction. Complexes 1 and 2 showed comparable catalytic activity for proton reduction to dihydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The limited examples reported include mostly hexacarbonyl and very few phosphine substituted mono‐ or diiron complexes [51–71] . Our group has also reported the redox and electrocatalytic properties of bis(monothiolato)‐based {FeFe} systems [72–77] wherein we have shown that the efficiency and stability of the catalysts vary with the type of monothiolate ligand used.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The limited examples reported include mostly hexacarbonyl and very few phosphine substituted mono‐ or diiron complexes [51–71] . Our group has also reported the redox and electrocatalytic properties of bis(monothiolato)‐based {FeFe} systems [72–77] wherein we have shown that the efficiency and stability of the catalysts vary with the type of monothiolate ligand used.…”
Section: Introductionmentioning
confidence: 91%
“…The overpotentials (O.P, η / V) for catalysis by complexes 1 (0.76), 2 (1.06) and 3 (0.61) were calculated as reported in literature (η = E cat À E 0 HA ; E 0 HA = À 1.46 V for AcOH) [108][109] and were comparable to similar reported complexes (Table 2). [54,72,[79][80] Catalytic efficiencies (C.E.) for complexes 1-3 in AcOH were calculated to be ∼ 0.90-0.14 (1), 0.94-0.48 (2) and 0.88-0.38 (3).…”
Section: Chemistryselectmentioning
confidence: 99%